Making Medicines in Africa The Political Economy of Industrializing for Local Health - Mackintosh, Maureen; Banda, Geoffrey; Tibandebage, Paula; Wamae, Watu (International Political Economy Series, 2016)
This book is open access under a CC-BY license. The importance of the pharmaceutical industry in Sub-Saharan Africa, its claim to policy priority, is rooted in the vast unmet health needs of the sub-continent. Making Medicines in Africa is a collective endeavour, by a group of contributors with a strong African and more broadly Southern presence, to find ways to link technological development, investment and industrial growth in pharmaceuticals to improve access to essential good quality medicines, as part of moving towards universal access to competent health care in Africa. The authors aim to shift the emphasis in international debate and initiatives towards sustained Africa-based and African-led initiatives to tackle this huge challenge. Without the technological, industrial, intellectual, organisational and research-related capabilities associated with competent pharmaceutical production, and without policies that pull the industrial sectors towards serving local health needs, the African sub-continent cannot generate the resources to tackle its populations' needs and demands.    Research for this book has been selected as one of the 20 best examples of the impact of UK research on development. See http://www.ukcds.org.uk/the-global-impact-of-uk-research for further details.